PERANAN POLITIK DALAM MENCIPTAKAN PEMERINTAHAN YANG BAIK - SALASIAH SALASIAH (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
The aim of this research is to know about the role of the politics towards the good governance.The background of it is that the state offIcer has not executed the good governance well in serving the public.The theory of the good governance shows the behaviours namely : cooprative, participative, transparant, accountable,and reliable.The method of the research is library one by finding-out data from the mass-media.The results of the research are that the most of the state oficers are not carrying out the priciples of good governce.The suggestions of the researcher are (1). To have the good examples of the elites (2).The superviser has to work hard to control (3).To give punishment and reewards as well to the staff..